Effect of preoperative hair removal vs. no removal on surgical site infections: a systematic review and meta-analysis [version 1; peer review: 2 approved] - Abdulsalam Aleid; Zainab Aleid; Abdulmajeed Aljabr; Abdulrahman Almoslem; Lama AlOraini; Mutlaq Alsubaie; Abdulaziz Alharthi; Hasan Ali Abdullah Alaidarous; Saud Nayef Aldanyowi; Abbas Al Mutair (F1000Research)
Background The practice of preoperative hair removal has been debated regarding its role in Surgical Site Infection (SSI) prevention. This study aimed to compare the different hair removing modalities and investigate the effect of preoperative hair removal on SSI rates. Methods A systematic review and meta-analysis were conducted according to PRISMA guidelines. Three databases—PubMed, Web of Science, and Cochrane Library—were searched for relevant studies comparing preoperative hair removal to no hair removal. Studies eligible for inclusion were randomized controlled trials (RCTs) and cohort studies reporting SSI rates. Odds ratios, mean differences, and p-values were analyzed using a random effect model. Results Seventeen studies involving 5,407 patients were included. No statistically significant difference in SSI rates was found between the hair removal and no removal groups (OR = 1.066, 95% CI 0.646–1.758, p = 0.803). When comparing clipping to no hair removal, there was no significant difference (OR = 0.967, 95% CI 0.642–1.455, p = 0.870). Razor shaving was associated with higher skin damage and slightly increased SSI risk compared to clipping but not statistically significant (OR = 0.749, 95% CI 0.346–1.623, p = 0.464). Depilatory creams, however, were favored over razor shaving (OR = 3.235, 95% CI 1.543–6.785, p = 0.002), as they were linked to less skin damage and easier application. Conclusion Preoperative hair removal does not significantly impact SSI rates. Clipping appears to be a safer alternative to shaving, while depilatory creams show promise as an effective, less damaging option.